2019
DOI: 10.1093/ajcn/nqz188
|View full text |Cite
|
Sign up to set email alerts
|

A randomized crossover trial assessing the effects of acute exercise on appetite, circulating ghrelin concentrations, and butyrylcholinesterase activity in normal-weight males with variants of the obesity-linked FTO rs9939609 polymorphism

Abstract: Background The fat mass and obesity-associated gene (FTO) rs9939609 A-allele is associated with higher acyl-ghrelin (AG) concentrations, higher energy intake, and obesity, although exercise may mitigate rs9939609 A-allele–linked obesity risk. Butyrylcholinesterase (BChE) hydrolyzes AG to des-acyl-ghrelin (DAG), potentially decreasing appetite. However, the effects of the FTO rs9939609 genotype and exercise on BChE activity, AG, DAG, and energy intake are unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 42 publications
8
39
0
Order By: Relevance
“…However, similar to our study, they found no difference in fasting concentrations of AG between genotypes, but when presented as a ratio of AG/des-acyl-ghrelin (DAG), AA genotype demonstrated higher levels compared to TT [13]. Interestingly, the Dorling et al [13] study also observed lower fasting butyrylcholinesterase (BChE) activity in carriers of AA compared to TT, which may offer a potential explanation for the reported higher AG:DAG ratio and energy intake between genotypes. BChE activity increases AG hydrolysis in plasma, leading to greater DAG and a lower AG:DAG ratio, which has been linked to lower energy consumption and lower adiposity in mice [12].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…However, similar to our study, they found no difference in fasting concentrations of AG between genotypes, but when presented as a ratio of AG/des-acyl-ghrelin (DAG), AA genotype demonstrated higher levels compared to TT [13]. Interestingly, the Dorling et al [13] study also observed lower fasting butyrylcholinesterase (BChE) activity in carriers of AA compared to TT, which may offer a potential explanation for the reported higher AG:DAG ratio and energy intake between genotypes. BChE activity increases AG hydrolysis in plasma, leading to greater DAG and a lower AG:DAG ratio, which has been linked to lower energy consumption and lower adiposity in mice [12].…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, Karra et al [11] observed elevated basal ghrelin mRNA expression in peripheral blood cells and reduced suppression of circulating ghrelin in FTO risk A-allele carriers within a subset of 20 individuals. In a comparable cohort, Dorling and colleagues also found an attenuated AG suppression after a fixed meal, which coincided with higher ad libitum energy intake compared with TT [13]. However, similar to our study, they found no difference in fasting concentrations of AG between genotypes, but when presented as a ratio of AG/des-acyl-ghrelin (DAG), AA genotype demonstrated higher levels compared to TT [13].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The cause of this discrepancy between the studies remained unclear. However, the relationship between FTO genotype and dietary intake seems to be very complex and many factors may have a role in this association such as the obesity [ 29 ], level of physical activity [ 19 ], serum leptin [ 30 ], and other dietary components [ 29 , 30 ]. However, only overweight subjects were included because of the possible effect of BMI on the association between FTO genotype and dietary intake.…”
Section: Discussionmentioning
confidence: 99%